2002
DOI: 10.2214/ajr.179.2.1790477
|View full text |Cite
|
Sign up to set email alerts
|

Application of Oral Contrast Media in Coregistered Positron Emission Tomography—CT

Abstract: An oral contrast agent can be used for coregistered PET-CT without the introduction of artifacts in PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…However, this phenomenon does not seem to have much clinical effect. No significant difference in the distribution of intense FDG uptake in the intestinal regions was shown by DIZENDORF et al [29] in a study of two groups of 30 patients each. To minimise these artefacts, low-density barium appears to be suitable for clinical use [30]; administration of a negative oral contrast agent using mannitol is also promising [31].…”
Section: Value Of Integrated Pet/ct W De Wever Et Almentioning
confidence: 74%
“…However, this phenomenon does not seem to have much clinical effect. No significant difference in the distribution of intense FDG uptake in the intestinal regions was shown by DIZENDORF et al [29] in a study of two groups of 30 patients each. To minimise these artefacts, low-density barium appears to be suitable for clinical use [30]; administration of a negative oral contrast agent using mannitol is also promising [31].…”
Section: Value Of Integrated Pet/ct W De Wever Et Almentioning
confidence: 74%
“…Several other investigators have recently confirmed the feasibility of using intravenous contrast in various types of modified injection protocols allowing combined diagnostic CT with PET (10-12). Oral contrast may affect the CT-based attenuation (2,13,14). The resulting attenuation-corrected PET activity can be overestimated by as much as 20%, but with an average of 4.4% with standard dilutions of positive oral contrast (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…In oncologic PET/CT, the use of intravenous enhanced CT data for attenuation correction has been found to produce image artifacts when the bolus injection results in high concentrations of contrast agent (11,12). However, other studies suggest that for tumor staging, this biased quantification usually does not change the diagnostic decision (13)(14)(15)(16)(17), especially if non-attenuationcorrected images are read alongside. This type of artifact can also be observed in cardiac PET/CT, especially in the region of the superior and inferior cava veins (3), and is likely to be more pronounced because CT coronary angiography requires data acquisition during an early arterial phase when the concentration of contrast agent in the blood is high, whereas oncologic CT is often acquired during the venous phase, when blood concentrations are lower.…”
Section: Discussionmentioning
confidence: 99%